2014
DOI: 10.1111/joa.12169
|View full text |Cite
|
Sign up to set email alerts
|

Regional molecular and cellular differences in the female rabbit Achilles tendon complex: potential implications for understanding responses to loading

Abstract: The aim of this study was: (i) to analyze the morphology and expression of extracellular matrix genes in six different regions of the Achilles tendon complex of intact normal rabbits; and (ii) to assess the effect of ovariohysterectomy (OVH) on the regional expression of these genes. Female New Zealand White rabbits were separated into two groups: (i) intact normal rabbits (n = 4); and (ii) OVH rabbits (n = 8). For each rabbit, the Achilles tendon complex was dissected into six regions: distal gastrocnemius (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Tendon tissues of the LG, MG, and FDS region were taken 3 cm proximal of the calcaneus; this is the location that was anticipated to be most affected by the repetitive motion . The paratenon was collected separately followed by splitting the Achilles tendon complex in the LG, MG, and FDS as described previously . The tissues from each region were divided; samples for mRNA expression and protein level analysis were snap frozen using liquid nitrogen and stored at −80°C until further analysis, and samples for histological analysis were fixed in 10% formalin in phosphate‐buffered saline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tendon tissues of the LG, MG, and FDS region were taken 3 cm proximal of the calcaneus; this is the location that was anticipated to be most affected by the repetitive motion . The paratenon was collected separately followed by splitting the Achilles tendon complex in the LG, MG, and FDS as described previously . The tissues from each region were divided; samples for mRNA expression and protein level analysis were snap frozen using liquid nitrogen and stored at −80°C until further analysis, and samples for histological analysis were fixed in 10% formalin in phosphate‐buffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…The four regions of the rabbit Achilles tendon complex assessed in this study; FDS, flexor digitorum superficialis; LG, lateral gastrocnemius; MG, medial gastrocnemius; P, paratenon. Original art by Gustav Andersson, reproduced and adapted with permission.…”
Section: Methodsmentioning
confidence: 99%
“…Bridgeman et al observed both ERα and ERβ in normal and disease tendon of male and female patients, without any statistically significant difference. On the other hand the impact of ovariohysterectomy (OVH) on gene expression in rabbit resulted different in various tendons that may indicate variances in number and distribution of oestrogen receptors 43,44 . Oestrogen level has a direct effect on collagenous tissue in severalpreclinical studies.…”
Section: Oestrogen Deficiency and Tendon: Preclinical And Clinical Fimentioning
confidence: 99%
“…36,37 It should be noted that oestrogen might exert different effects on the biomechanical properties of tendons due to disparities in the loading profile and differences in the relative distribution and numbers of oestrogen receptors. 38,39 Our recent study demonstrated that the absence of ERβ leads to abnormalities in Achilles tendon healing at the early stage and that these are mainly characterized by increased adipocyte accumulation. 6 However, whether and how ERβ affects Achilles tendon repair after the early healing stage.…”
Section: Discussionmentioning
confidence: 99%